Continuous-time random walks and synchronization on circulant networks - Garcia, Emmanuel Soliman M. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2009)
We study random walks on circulant networks and present a continuous time generalization that considers uncorrelated waiting times which have a finite mean. The properties of this continuous-time random walk (CTRW) can be related to their equivalent properties in the discrete-time random walk, which were previously derived in the literature using spectral techniques. Using these relations leads to exact expressions for 1) the probability for a random walker starting at one node to be at another node at a certain time t, and 2) the mean first- passage time (MFPT) between a pair of distinct nodes.